Use of CPR feedback devices in resuscitation training: A systematic review and meta-analysis of randomized controlled trials - Yiqun Lin; Andrew Lockey; Aaron Donoghue; Robert Greif; Andrea Cortegiani; Barbara Farquharson; Fahad Javaid Siddiqui; Arna Banerjee; Tasuku Matsuyama; Adam Cheng (Resuscitation Plus)
Objectives: The use of cardiopulmonary resuscitation (CPR) feedback devices during training is increasing. This review evaluates whether incorporating CPR feedback devices in training improves patient survival, CPR quality in actual resuscitation, skill acquisition and retention after training. Methods: This systematic review was part of the continuous evidence evaluation process of the International Liaison Committee on Resuscitation (ILCOR). We searched MEDLINE, EMBASE, and SCOPUS databases from inception to September 30, 2024, including randomized controlled trials (RCTs) in all languages (with an English abstract) comparing CPR training with and without feedback devices. Outcome included patient survival, quality of clinical performance in resuscitation, and CPR skill acquisition and retention. Non-RCT studies, unpublished work without peer review or animal studies were excluded. Risk of bias was assessed using Cochrane tools, and certainty of evidence was graded using the Grading of Recommendations Assessment, development and Evaluation (GRADE) approach. Standardized mean difference (SMD) were calculated and pooled effects were analyzed using random-effects models. PROSPERO CRD42023488130. Results: We identified 20 RCTs with 4579 participants. Risks of bias ranged from low to critical (low: 8, moderate: 9, and critical: 3). No studies evaluated the patient survival, clinical performance in resuscitation or cost-effectiveness. Compared to no feedback, using CPR feedback devices during training significantly improved key quality metrics. Pooled effect sizes were 0.76 (95%CI 0.02 – 1.50) for mean compression depth (15 studies), 0.98 (95%CI: 0.10 – 1.87) for depth compliance (16 studies), 0.29 (95%CI: 0.10 – 0.48) for mean rate (17 studies), 0.44 (95%CI: 0.23 – 0.66) for rate compliance (9 studies), and 0.53 (95%CI: 0.31 – 0.75) for recoil compliance (10 studies) in favour of using feedback devices during training. Heterogeneity was large (I2 > 50%) in all analyses. Planned subgroup analyses revealed no statistically significant interaction between healthcare professionals and laypersons. Using the GRADE approach, the certainty of evidence was downgraded for certain outcomes due to critical risk of bias for 3 studies and inconsistency but upgraded for strong association. Conclusion: The use of CPR feedback devices during resuscitation training improves key quality metrics of CPR performance, with moderate to high certainty of evidence. However, further studies are needed to evaluate the impact on cost-effectiveness, clinical performance and patient outcomes.